Pengaruh Gaya Kepemimpinan Kerja Disiplin Kerja Motivasi Kerja Terhadap Kinerja Karyawan (Studi Pada Rs. Dr. Moewardi Jebres Surakarta) - Hersianawaty, Salsabilla; , Agus Muqorrobin, Drs., M.M (2016)
This study was conducted to investigate the effect of variable Style of Leadership, Discipline of work and work motivation on employee performance RS. Dr. Moewardi Jebres. This study uses data collection methods that included interviews and questionnaires. The number of respondents in this study were 50 employees of the hospital. Dr. Moewardi Jebres obtained through random sampling techniques. Mechanical testing data used in this study are: 1. Test instrument data includes data validity test and reliability test data 2. Test the hypothesis includes multiple linear analysis, F test, T test, and test R2, 3. classic assumption test include tests normality, heteroscedasticity test, test multicollinearity and autocorrelation test. Results of the analysis showed that the leadership style of positive and significant effect on the performance of employees, work discipline and significant positive effect on employee performance, motivation and significant positive effect on employee performance. Keywords: Leadership Style, Work Discipline, Work Motivation and Employee Performance